Patterning: Atomic‐Level Sculpting of Crystalline Oxides: Toward Bulk Nanofabrication with Single Atomic Plane Precision (Small 44/2015). Issue 44 (November 2015) - Jesse, Stephen; He, Qian; Lupini, Andrew R.; Leonard, Donovan N.; Oxley, Mark P.; Ovchinnikov, Oleg; Unocic, Raymond R.; Tselev, Alexander; Fuentes‐Cabrera, Miguel; Sumpter, Bobby G.; Pennycook, Stephen J.; Kalinin, Sergei V.; et al.
Abstract : On page 5895, Q. He, A. Y. Borisevich, and co‐workers describe how an aberration‐corrected e‐beam in a scanning transmission electron microscope can be used to crystallize amorphous complex oxides with atomic plane precision. Using this control system, epitaxial growth of SrTiO3 is achieved to pattern text onto a 90 × 25 nm area, as shown in the image. Each feature shown is about 20 unit cells (about 8 nm) wide.